2020
DOI: 10.3390/geosciences10040140
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Emissions from Quartz Subjected to Shear Stress: Spectral Signatures and Geophysical Implications

Abstract: Shear tests on quartz rocks and single quartz crystals have been conducted to understand the possible relationship between the intensity of detectable stress in fault areas and the energy released in the form of electromagnetic waves in the range 30 KHz-1 MHz (LF–MF). For these tests, a new type of piston-cylinder has been developed, instrumented to collect the electromagnetic signals generated by the quartz during shear stress tests and that allows energy measurements on electromagnetic emissions (EMR) to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
4
19
0
Order By: Relevance
“…The data obtained in this study should be seen in the light of the most recent literature on the effects of shear stress on alpha quartz, literature to which the authors have also contributed [5,6]. The fractures we have observed show an evolution which, we believe, depends substantially on the stress rate rather than on the pressure itself.…”
Section: Discussion Of Datasupporting
confidence: 68%
See 4 more Smart Citations
“…The data obtained in this study should be seen in the light of the most recent literature on the effects of shear stress on alpha quartz, literature to which the authors have also contributed [5,6]. The fractures we have observed show an evolution which, we believe, depends substantially on the stress rate rather than on the pressure itself.…”
Section: Discussion Of Datasupporting
confidence: 68%
“…The task of this experimental work is to understand the mechanisms that link the progressive demolition of the crystal structure of quartz and the appearance of polymorphic phases during the application of sliding stresses. In two previous works [5,6], the authors of this work reported details on the polymorphic phases of silica that are formed during fracturing and on the correlations between fractures and the amount of very low frequency electromagnetic energy emitted by the crystals during the fracturing.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations